Correlation Between Dysminorrhea Incidence and Student’s Grade Point - Kusumawati, Estri; Lusiana, Nova (International Conference on Sustainable Health Promotion, 2018)
Adolescence is a period of transitions children toward adulthood. Teenagers experience many changes to either physical or psychic; physical changes are characterized by the maturity of the reproductive organs. The timeline of these, starting with the onset of menstruation, teen not uncommon experience painful menstruation (dysmenorrhea). Dysmenorrhea often interferes with daily activities including learning activities. Learning activities that disturbed the learning achievements may cause a decline in students. The purpose of this research is to know the correlation of the incidence of dysmenorrhea with the student achievement index. The population in this research is a biology study program of Sunan Ampel Islamic University Surabaya. The sampling techniques used in this research is quota sampling. The number of samples used is 60 respondents. Statistical tests used were chi-square with 0.05 significance level. From the results of the analysis of the data by using the chi-square test results obtained by the significance of 0.722 (0.722 > 0.05), so that it can be concluded that there is no correlation between the incidence of dysmenorrhea and grade point of a student.